Analysis of Community Readiness for the Mandalika Special Economic Zone: Using the Sapta Pesona Standard - Muhammad Azizurrohman; Gunawan Bata Ilyas; Yanti Mayasari Ginting; Sudiyanti Sudiyanti; Yulia Nur Hasanah (Journal of Economics Research and Social Sciences, 2023)
The Mandalika Special Economic Zone is one of the locations selected as a priority destination by the Government of Indonesia. Therefore, this opportunity must be utilized by the surrounding community in order to get the maximum benefit. This study aims to assess the readiness of the community in carrying out tourism-based development. Identify readiness both as a host and as a tourism business actor based on the Sapta Pesona standard. Based on the results of the analysis, it is known that the people around the Mandalika Special Economic Zone are quite ready to take advantage of tourism activities. However, the standard of safety and serenity is still not as expected. Thus, there is still a need for improvement in terms of security and additional green open space to add to the coolness of the Mandalika area.